Ticagrelor regulates osteoblast and osteoclast function and promotes bone formation in vivo via an adenosine‐dependent mechanism. Issue 11 (10th August 2016) - Mediero, Aránzazu; Wilder, Tuere; Reddy, Vishnu S. R.; Cheng, Qian; Tovar, Nick; Coelho, Paulo G.; Witek, Lukasz; Whatling, Carl; Cronstein, Bruce N.
ABSTRACT: As many as 10% of bone fractures heal poorly, and large bone defects resulting fromtrauma, tumor, or infection may not heal without surgical intervention. Activation of adenosine A2A receptors (A2A Rs) stimulates bone formation. Ticagrelor and dipyridamole inhibit platelet function by inhibiting P2Y12 receptors and platelet phosphodiesterase, respectively, but share the capacity to inhibit cellularuptake of adenosine and thereby increase extracellular adenosine levels. Because dipyridamole promotes bone regeneration by an A2A R‐mediated mechanism we determined whether ticagrelor could regulate the cells involved in bone homeostasis and regeneration in a murine model and whether inhibition of P2Y12 or indirect A2A R activation via adenosine was involved. Ticagrelor, dipyridamole and the active metabolite of clopidogrel (CAM), an alternative P2Y12 antagonist, inhibited osteoclast differentiation and promoted osteoblast differentiation in vitro . A2A R blockade abrogated the effects of ticagrelor and dipyridamole on osteoclast and osteoblast differentiation where as A2B R blockade abrogated the effects of CAM. Ticagrelor and CAM, when applied to a 3‐dimentional printed resorbable calcium‐triphosphate/ hydroxyapatite scaffold implanted in a calvarial bone defect, promoted significantly more bone regeneration than the scaffold alone and as much bone regeneration as BMP‐2, a growth factor currently used to promote bone regeneration. These results suggest novel approaches to targeting adenosine receptors in the promotion of bone regeneration.—Mediero, A., Wilder, T., Reddy, V. S. R., Cheng, Q., Tovar, N., Coelho, P. G., Witek, L., Whatling, C., Cronstein, B. N. Ticagrelor regulates osteoblast and osteoclast function and promotes bone formation in vivo via an adenosine‐dependent mechanism. FASEB J. 30, 3887–3900 (2016) www.fasebj.org